Body size and premolar evolution in the early‐middle eocene euprimates of Wyoming. Issue 1 (18th October 2013) - Jones, Katrina E.; Rose, Kenneth D.; Perry, Jonathan M.G.
ABSTRACT The earliest euprimates to arrive in North America were larger‐bodied notharctids and smaller‐bodied omomyids. Through the Eocene, notharctids generally continued to increase in body size, whereas omomyids generally radiated within small‐ and increasingly mid‐sized niches in the middle Eocene. This study examines the influence of changing body size and diet on the evolution of the lower fourth premolar in Eocene euprimates. The P4 displays considerable morphological variability in these taxa. Despite the fact that most studies of primate dental morphology have focused on the molars, P4 can also provide important paleoecological insights. We analyzed the P4 from 177 euprimate specimens, representing 35 species (11 notharctids and 24 omomyids), in three time bins of approximately equal duration: early Wasatchian, late Wasatchian, and Bridgerian. Two‐dimensional surface landmarks were collected from lingual photographs, capturing important variation in cusp position and tooth shape. Disparity metrics were calculated and compared for the three time bins. In the early Eocene, notharctids have a more molarized P4 than omomyids. During the Bridgerian, expanding body size range of omomyids was accompanied by a significant increase in P4 disparity and convergent evolution of the semimolariform condition in the largest omomyines. P4 morphology relates to diet in early euprimates, although patterns vary between families. Am J Phys Anthropol 153:15–28, 2014. © 2013 Wiley Periodicals, Inc.